Realization of Assertive Acts by Nemo in Finding Nemo the Movie - Kormia Dewi, Kadek Novi; Qomariana, Yana (Humanis; Vol 25 No 1 (2021)DO - 10.24843/JH.2021.v25.i01.p11, 2021)
This article is focused on the function of assertive act and the delivery strategies used by Nemo in Finding Nemo the movie. The data was collected by using documentation method and note taking technique. The collected data was analyzed by using descriptive qualitative method and was presented using informal method. The theories applied in this article were a theory of illocutionary act proposed by Searle (1976) to classify the functions of assertive act and a theory of delivery strategies proposed by Parker (1986). The result of the analysis showed that there were six functions of assertive act found in Finding Nemo the movie, those are affirming, predicting, claiming, agreeing, informing, and denying. However, there are only three strategies used by Nemo to deliver the messages of his utterances.